Quality of the design of removable partial dentures in working models - Calzada Gonzales, Nancy (2019)
Objective. was to determine the quality of removable partial denture (RP) design in working models performed in Huánuco as of 2017 according to the years of experience of the professionals. Methods. This is a descriptive level, cross-sectional, basic and prospective study. Under a quantitative approach, 280 working models for the fabrication of removable partial dentures were included in the study. Samples were collected in dental laboratories in the city of Huánuco. The components of the PPR design were observed for each sample. Descriptive statistics were applied. Results. 73 (91.3 %) did not carry out the shipping order (instructions from the dental professional about the design that the PPR should have), delegating the choice of the design to the dental laboratory technician and in a lower percentage did the instructions for the elaboration of the PPR 7 (8.8 %), 51 working models were upper dental arches and in a lower percentage, 29 (36.3 %) were the lower dental arches. The design quality of the removable partial denture bases in working models was acceptable in a total of 46 models. Conclusion. The quality of the design of the removable partial dentures was incorrect in a high percentage of cases; the components that make up the prosthesis did not comply with the ideal characteristics. 22.86 % of the dentists sent the working models with the design for the fabrication of the removable partial prosthesis.